Big oil even bigger : ConocoPhillips acquires Devon Energy - Foss, Sivert Rossnes (2024)
The US exploration and production (E&P) industry is experiencing a major consolidation trend, led by strong balance sheets and a focus on lowering production costs as the global demand for oil is expected to decline. In the last year, ConocoPhillips has seen some of its peers pursue mega acquisitions. Therefore, to ensure their market position, this thesis analyses a potential acquisition of Devon Energy by ConocoPhillips. By valuing each firm as a standalone company and synergies arising from the potential merger, an offer price of 58 USD, 15% above the current market price, is proposed to offer Devon in a friendly takeover. Net synergies arising from the transaction are estimated to be 4,21 billion USD, and financing is obtained through taking on new debt of 35,4 billion USD and 2,6 billion USD in excess cash. Because of Devon’s low reserves-to-production ratio, the newly acquired debt is expected to be managed by cash flows from Devon’s already developed reserves. Strategically, the merger is favourable as it allows ConocoPhillips to exploit the high expected commodity prices in the short term while mitigating long-term commodity price risk. Therefore, based on financial and strategic reasoning, ConocoPhillips is recommended to pursue the proposed transaction.